Confronting Crisis : Global Cooperation and the International Monetary Fund - Procopio, Joe. (Washington, D.C. : International Monetary Fund, 2014)
A history of the origins and 70-year history of the IMF as told in graphic novel form.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet